The Role of Individual Domains and the Significance of Shedding of ATP6AP2/(pro)renin Receptor in Vacuolar H+-ATPase Biogenesis - Kinouchi, Kenichiro; Ichihara, Atsuhiro; Sano, Motoaki; Sun-Wada, Ge-Hong; Wada, Yoh; Ochi, Hiroki; Fukuda, Toru; Bokuda, Kanako; Kurosawa, Hideaki; Yoshida, Naohiro; Takeda, Shu; Fukuda, Keiichi; et al. (PLOS ONE, 2013)
The ATPase 6 accessory protein 2 (ATP6AP2)/(pro)renin receptor (PRR) is essential for the biogenesis of active vacuolar H+-ATPase (V-ATPase). Genetic deletion of ATP6AP2/PRR causes V-ATPase dysfunction and compromises vesicular acidification. Here, we characterized the domains of ATP6AP2/PRR involved in active V-ATPase biogenesis. Three forms of ATP6AP2/PRR were found intracellularly: full-length protein and the N- and C-terminal fragments of furin cleavage products, with the N-terminal fragment secreted extracellularly. Genetic deletion of ATP6AP2/PRR did not affect the protein stability of V-ATPase subunits. The extracellular domain (ECD) and transmembrane domain (TM) of ATP6AP2/PRR were indispensable for the biogenesis of active V-ATPase. A deletion mutant of ATP6AP2/PRR, which lacks exon 4-encoded amino acids inside the ECD (Δ4M) and causes X-linked mental retardation Hedera type (MRXSH) and X-linked parkinsonism with spasticity (XPDS) in humans, was defective as a V-ATPase-associated protein. Prorenin had no effect on the biogenesis of active V-ATPase. The cleavage of ATP6AP2/PRR by furin seemed also dispensable for the biogenesis of active V-ATPase. We conclude that the N-terminal ECD of ATP6AP2/PRR, which is also involved in binding to prorenin or renin, is required for the biogenesis of active V-ATPase. The V-ATPase assembly occurs prior to its delivery to the trans-Golgi network and hence shedding of ATP6AP2/PRR would not affect the biogenesis of active V-ATPase.